Digital-Based Economic Resilience: Analysis Of Facebook Commerce Role In Enhancing Economic Independence Of Women Daily Business Actors In Ipuh District, Mukomuko Regency, Bengkulu - Nining Septia; Ahmad Soleh; Muhammad Rahman Febliansa (Universitas Dehasen Bengkulu, 2026)
The development of the digital economy has opened new opportunities for women micro-entrepreneurs in rural areas to enhance their economic independence through social media utilization. This study aims to analyze the role of Facebook Commerce in strengthening digital-based economic resilience and the independence of women daily business actors in Ipuh District, Mukomuko Regency, Bengkulu. Using a quantitative descriptive method, data were collected through online questionnaires (Google Forms) from 40 women entrepreneurs actively using Facebook for business promotion and sales. The results show that 92.5% of respondents use Facebook daily for marketing, dominated by the culinary (45%), fashion (22.5%), and service (17.5%) sectors. About 72.5% experienced income growth, 95% expanded their market reach, and 97.5% felt more financially independent and flexible in managing work time. The main challenges include poor internet connectivity (42.5%), limited capital (37.5%), and lack of digital training access (42.5%). Strong family support (92.5%) and self-learning motivation were key factors in digital adaptation. This study concludes that Facebook Commerce serves as a strategic catalyst for women's empowerment and digital economic resilience in rural communities, offering an empirical foundation for inclusive gender-based digital empowerment policies.